The changing face of colonial education in Africa: Education, science and development - Duncan, Graham (HTS teologiese studies, 2022)
This review article enters into discussion with Peter Kallaway, in his work, The Changing Face of Colonial Education in Africa: Education, Science and Development, who raises serious issues related to the historical development of South Africa’s education during the first half of the 19th century and its current situation and future prospects in the broader context of African education. Education is a dynamic process that encompasses the formal and informal sectors historically. In South Africa, the informal was the norm for centuries before the intrusion of Western influences and formal education needs to work alongside the informal processes based in the home, the church and the community. Formal education is a product of the West and came to occupy the determinative place in the period covered by this book, while the informal sector was relegated to a subservient role despite its inherent value. Kallaway discusses these issues by analysing the contributions of external factors such as the International Missionary Council in the religious sphere and the New Education Fellowship and the British colonial service in the secular sphere. These played a significant role in the movement from ‘culture-bound’ to a universalised approach to education in Africa and particularly South Africa. Alongside this, the role of mission education is discussed as a source of tension with external forces and as a significant contributor to the development of education not restricted to the religious domain. Mission education emerges as an innovative force in educational development as a part of the international movement within the context of an emerging ‘development’ paradigm. The external and internal forces and the cultural and universalising are not necessarily in opposition to one another but often in conversation with and in tension with one another’s assumptions. Kallaway undertakes two case studies of South African scholars, Donald M’Timkulu and SEK Mqhayi in order to refine his analysis. It has been alleged with truth that the trader and settler followed the missionary, who was the agent of European imperialism, working hand in hand with the colonial powers for the subjugation of the black people and the territorial extension of the imperialist power. This view has been challenged by Brian Stanley who cautions against a too simplistic interpretation of the relationship between colonisation and Christianisation reached through ideological means rather than intensive historical research. He concludes that the process first appears more complex and seeks to avoid generalisations. This provides an appropriate starting point for this review article, which attempts to go beyond the historical by raising contemporary issues related to the concept of Africanisation.Contribution: This article contributes to the ongoing debate regarding developments in education in a colonial context from a historical perspective. This is relevant to current debates and challenges to the ongoing effects of colonisation in education in a democratic society and the prospect of an epistemological shift towards the Africanisation of education.